KAJIAN WILAYAH POTENSI PENYEBARAN COVID-19 MENGGUNAKAN PENDEKATAN ANALITIK DENGAN ELLIPS KESALAHAN - Aulia, Miya; Armijon, Armijon; Murdapa, Fauzan (Department of Geodesy and Geomatics, University of Lampung, 2023)
The error ellipsoid method is used to analyze the distribution or spread of people exposed to Covid-19 in Sukarame District, Sukarame District. The spatial distribution or spread pattern of Covid-19 (location) was analyzed using an error ellipsoid from the standard deviation results of the patient's distance to the center of the high distribution location to understand the direction of spread of Covid-19. From the results of the analysis, it can be seen that the pattern of Covid-19 spread as a whole and has a movement in a certain direction indicated by the center of gravity or centroid. This study discusses the potential spread of Covid-19 in Sukarame District by utilizing the elliptical error method. The purpose of this thesis is to determine the direction of movement of the potential spread of Covid-19 in Sukarame District. The use of this error ellipsoid method is to focus on preventing or reducing people exposed to Covid-19 by knowing the movement of the spread of Covid-19 so that the government can issue policies that are expected to reduce the potential spread of Covid-19 in Sukarame District.Kata kunci: elips kesalahan, Covid-19, Potensi Penyebaran, Sukarame